Histological effects of linear alkyl benzene sulfonic acid exposure on primordial germ cell migration and gonad formation in zebrafish (Danio rerio) - Akbulut, Cansu; Yön, Nazan Deniz (Archives of Biological Sciences, 2019)
Paper description: Primordial germ cells are embryonic stem cells that migrate into gonadal ridges to form gametes and their migration is crucial for gonad formation. The histological effects of linear alkyl benzene sulphonic acid, used as an anionic surfactant in detergents, on the development of the reproductive system of zebrafish embryos was examined. Zebrafish embryos received 0.25, 0.5 and 1 mg/L linear alkyl benzene sulphonic acid and samples were collected for 60 days. Linear alkyl benzene sulphonic acid exposure disrupted the migration path of primordial germ cells, revealed as delayed gonadal development and sex differentiation. Abstract: The use of detergents has become widespread and is growing. The increase in population and use of detergent threatens the life of organisms in the ecosystem. In this study, the histological effects of linear alkyl benzene sulphonic acid on primordial germ cell (PGC) migration and gonad formation in zebrafish were investigated after application of 0.25 0.5 and 1 mg/L of linear alkyl benzene sulphonic acid to embryos. Samples of embryos and larvae were collected for 60 days and the effects of linear alkyl benzene sulphonic acid on PGC migration and gonad development were examined by histological procedures. The localization and migration pathway of PGCs and structures of the gonads were inspected by Periodic Acid Schiff (PAS), alkaline phosphatase, toluidine blue and Best’s carmine staining. Primordial germ cells were observed in ectopic regions and delayed gonadal development and histopathological changes in gonad structures were observed. We concluded that linear alkyl benzene sulfonic acid exposure has a negative effect on the reproduction system of zebrafish. https://doi.org/10.2298/ABS190323041A Received: May 23, 2019; Revised: July 8, 2018; Accepted: July 10, 2019; Published online: July 17; 2019 How to cite this article: Akbulut C, Yön ND. Histological effects of linear alkyl benzene sulfonic acid exposure on primordial germ cell migration and gonad formation in Zebrafish (Danio rerio). Arch Biol Sci. 2019;71(4):589-95.